Boost and buck topology based single phase AC-DC converters with low THD and high power factor - Kabir, Md Ashfanoor; Abedin, Amina Hasan; Rahman, Dhrubo; Mustafiz, Rubiya Binta; Choudhury, Mohammad Ali A Shoukat (© 2011 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2011 33rd International Telecommunications Energy Conference, INTELEC 2011; Amsterdam; Netherlands; 9 October 2011 through 13 October 2011 [© 2011 IEEE ] The conference paper's definite version is available at: http://doi.org/10.1109/INTLEC.2011.6099724